Thrombopoietin mutation in congenital amegakaryocytic thrombocytopenia treatable with romiplostim - Alessandro Pecci; Iman Ragab; Valeria Bozzi; Daniela De Rocco; Serena Barozzi; Tania Giangregorio; Heba Ali; Federica Melazzini; Mohamed Sallam; Caterina Alfano; Annalisa Pastore; Carlo L Balduini; et al. (EMBO Molecular Medicine)
Abstract Congenital amegakaryocytic thrombocytopenia (CAMT) is an inherited disorder characterized at birth by thrombocytopenia with reduced megakaryocytes, which evolves into generalized bone marrow aplasia during childhood. Although CAMT is genetically heterogeneous, mutations of MPL, the gene encoding for the receptor of thrombopoietin (THPO), are the only known disease‐causing alterations. We identified a family with three children affected with CAMT caused by a homozygous mutation (p.R119C) of the THPO gene. Functional studies showed that p.R119C affects not only ability of the cytokine to stimulate MPL but also its release, which is consistent with the relatively low serum THPO levels measured in patients. In all the three affected children, treatment with the THPO‐mimetic romiplostim induced trilineage hematological responses, remission of bleeding and infections, and transfusion independence, which were maintained after up to 6.5 years of observation. Recognizing patients with THPO mutations among those with juvenile bone marrow failure is essential to provide them with appropriate substitutive therapy and prevent the use of invasive and unnecessary treatments, such as hematopoietic stem cell transplantation or immunosuppression.